Pulmonary Bacterial Communities in Surgically Resected Noncystic Fibrosis Bronchiectasis Lungs Are Similar to Those in Cystic Fibrosis - Heather Maughan; Kristopher S. Cunningham; Pauline W. Wang; Yu Zhang; Marcelo Cypel; Cecilia Chaparro; D. Elizabeth Tullis; Thomas K. Waddell; Shaf Keshavjee; Mingyao Liu; David S. Guttman; David M. Hwang (Pulmonary Medicine)
Background. Recurrent bacterial infections play a key role in the pathogenesis of bronchiectasis, but conventional microbiologic methods may fail to identify pathogens in many cases. We characterized and compared the pulmonary bacterial communities of cystic fibrosis (CF) and non-CF bronchiectasis patients using a culture-independent molecular approach. Methods. Bacterial 16S rRNA gene libraries were constructed from lung tissue of 10 non-CF bronchiectasis and 21 CF patients, followed by DNA sequencing of isolates from each library. Community characteristics were analyzed and compared between the two groups. Results. A wide range of bacterial diversity was detected in both groups, with between 1 and 21 bacterial taxa found in each patient. Pseudomonas was the most common genus in both groups, comprising 49% of sequences detected and dominating numerically in 13 patients. Although Pseudomonas appeared to be dominant more often in CF patients than in non-CF patients, analysis of entire bacterial communities did not identify significant differences between these two groups. Conclusions. Our data indicate significant diversity in the pulmonary bacterial community of both CF and non-CF bronchiectasis patients and suggest that this community is similar in surgically resected lungs of CF and non-CF bronchiectasis patients.